Inspection of pathological manifestations in buildings using a thermal imaging camera integrated with an Unmanned Aerial Vehicle (UAV): a documented research - Da Silva, Willians Perlley Alexandre; Lordsleem Júnior, Alberto Casado; Ballesteros Ruiz, Ramiro Daniel; Aquino Rocha, Joaquin Humberto (Revista ALCONPAT, 2021)
This paper is intended to present usage of UAV integrated thermographic cameras in building inspection processes. This study was based on a systematic review of related articles and technical documents, in order to investigate features and basic operations of thermographic cameras, UAVs usage and influencing factors on detection of pathological manifestations. The results enabled identification of advantages and limitations for camera and UAV integration, thus demonstrating their feasibility and effectiveness when employed together. As a contribution, this study developed a flight protocol including steps and procedures required to perform an inspection using a thermal camera together with an UAV.